Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I came across this in a friend's 12th grade math homework and couldn't solve it. I want to factor the following trinomial: $$3x^2 -8x + 1.$$

How to solve this is far from immediately clear to me, but it is surely very easy. How is it done?

share|improve this question
    
Please don't write $+-8x$; it's the mathematical notation equivalent of chewing with your mouth open. –  Arturo Magidin Jun 20 '12 at 2:38
    
Also, how is this a trinomial? –  Eugene Jun 20 '12 at 2:39
    
If you know which values of $x$ make the quadratic$=0$ (such as through the quadratic formula), do you konw how to determine the factors of the quadratic? –  Cameron Buie Jun 20 '12 at 2:40
1  
@Eugene: Because there are three terms. –  Cameron Buie Jun 20 '12 at 2:41
    
@CameronBuie Ah. I mistakenly thought a trinomial was a term with $3$ variables. –  Eugene Jun 20 '12 at 2:44

4 Answers 4

up vote 2 down vote accepted

Hint: Use the quadratic formula.

share|improve this answer

We have the following theorem (Viéte formulae) for the quadratic case:

If $\,\alpha\,,\,\beta\,$ are roots (i.e., solutions) of the quadratic equation $\,ax^2+bx+c=0\,$ , then we have that$$ax^2+bx+c=a(x-\alpha)(x-\beta)$$

This is the reason why Eugene hinted you at using the quadratic formula

share|improve this answer

A standard way of factorizing, when it is hard to guess the factors, is by completing the square. \begin{align} 3x^2 - 8x + 1 & = 3 \left(x^2 - \dfrac83x + \dfrac13 \right)\\ & (\text{Pull out the coefficient of $x^2$})\\ & = 3 \left(x^2 - 2 \cdot \dfrac43 \cdot x + \dfrac13 \right)\\ & (\text{Multiply and divide by $2$ the coefficient of $x$})\\ & = 3 \left(x^2 - 2 \cdot \dfrac43 \cdot x + \left(\dfrac43 \right)^2 - \left(\dfrac43 \right)^2 + \dfrac13 \right)\\ & (\text{Add and subtract the square of half the coefficient of $x$})\\ & = 3 \left(\left(x - \dfrac43 \right)^2 - \left(\dfrac43 \right)^2 + \dfrac13 \right)\\ & (\text{Complete the square})\\ & = 3 \left(\left(x - \dfrac43 \right)^2 - \dfrac{16}9 + \dfrac13 \right)\\ & = 3 \left(\left(x - \dfrac43 \right)^2 - \dfrac{16}9 + \dfrac39 \right)\\ & = 3 \left(\left(x - \dfrac43 \right)^2 - \dfrac{13}9\right)\\ & = 3 \left(\left(x - \dfrac43 \right)^2 - \left(\dfrac{\sqrt{13}}3 \right)^2\right)\\ & = 3 \left(x - \dfrac43 + \dfrac{\sqrt{13}}3\right) \left(x - \dfrac43 - \dfrac{\sqrt{13}}3\right)\\ & (\text{Use $a^2 - b^2 = (a+b)(a-b)$ to factorize}) \end{align} The same idea works in general. \begin{align} ax^2 + bx + c & = a \left( x^2 + \dfrac{b}ax + \dfrac{c}a\right)\\ & = a \left( x^2 + 2 \cdot \dfrac{b}{2a} \cdot x + \dfrac{c}a\right)\\ & = a \left( x^2 + 2 \cdot \dfrac{b}{2a} \cdot x + \left( \dfrac{b}{2a}\right)^2 - \left( \dfrac{b}{2a}\right)^2 + \dfrac{c}a\right)\\ & = a \left( \left( x + \dfrac{b}{2a}\right)^2 - \left( \dfrac{b}{2a}\right)^2 + \dfrac{c}a\right)\\ & = a \left( \left( x + \dfrac{b}{2a}\right)^2 - \dfrac{b^2}{4a^2} + \dfrac{c}a\right)\\ & = a \left( \left( x + \dfrac{b}{2a}\right)^2 - \left(\dfrac{b^2-4ac}{4a^2} \right)\right)\\ & = a \left( \left( x + \dfrac{b}{2a}\right)^2 - \left(\dfrac{\sqrt{b^2-4ac}}{2a} \right)^2\right)\\ & = a \left( x + \dfrac{b}{2a} + \dfrac{\sqrt{b^2-4ac}}{2a}\right) \left( x + \dfrac{b}{2a} - \dfrac{\sqrt{b^2-4ac}}{2a}\right)\\ \end{align}

share|improve this answer

There's an approach called (by some) the "$ac$ method". Suppose $\alpha,\beta,\gamma,\delta$ are some constants, and consider the expansion $$(\alpha x+\beta)(\gamma x+\delta)=\alpha\gamma x^2+(\alpha\delta+\beta\gamma)x+\beta\delta=ax^2+bx+c.$$ Note that $\alpha\delta$ and $\beta\gamma$ are factors of $ac=\alpha\beta\gamma\delta$ and that $b=\alpha\delta+\beta\gamma$. In fact, they are paired factors of $ac$, in that $\alpha\delta\cdot\beta\gamma=ac$. The idea of the $ac$ method of factoring is to find such paired factors of $ac$ whose sum is $b$.

To see how this can be useful, consider the example $3x^2+13x-10$. Here, $ac=-30$ and $b=13$. We need to find two numbers that add up to $13$ and multiply to get $-30$. The only pair that works is $15$ and $-2$. Thus, we can rewrite $13$ as $15-2$ or $-2+15$. How is this useful? Well, $$3x^2+13x-10=3x^2+15x-2x-10=3x(x+5)-2(x+5)=(3x-2)(x+5)$$ and $$3x^2+13x-10=3x^2-2x+15x-10=x(3x-2)+5(3x-2)=(x+5)(3x-2),$$ so either way, we obtain our factorization without too much difficulty.

In this case, unfortunately, we have $ac=3$ and $b=-8$, so there is no obvious pair of factors! Such a pair does exist, namely $-4+\sqrt{13}$ and $-4-\sqrt{13}$, but even knowing the pair may not make the factorization simple in all cases (in this case it is, because $c=1$).

In general, if trying to factor something intractible to the $ac$ method, I recommend completing the square, as Marvis has demonstrated so well.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.